Pengaruh Store Atmosphere, Service Quality, Dan Harga Terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Pada Konsumen Consina Store Dinoyo) - Octavia Dwi Kumala; M. Hufron; Khalikus sabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract This study aims to analyze the direct and indirect effects of five variables, namely store atmosphere, service quality, price, customer satisfaction, and Customer Loyalty. The population of this research is all consumers of Dinoyo Consina store. Samples were taken using the accidental sampling method so that 96 respondents who met the requirements as samples. This research was conducted by distributing questionnaires. The results of this study indicate that the store atmosphere, service quality and price variables have a direct effect on customer satisfaction, store atmosphere, service quality and price variables have a direct effect on customer loyalty, customer satisfaction has a direct effect on customer loyalty and store atmosphere, service quality and price variables has an indirect effect on customer loyalty through customer satisfaction as an intervening variable. Keywords: store atmosphere, service quality, price, customer satisfaction, customer loyalty